"And our Mother from in Heaven": Death and Love in a Mexican Courtship Diary, Guadalajara, 1864–69. Issue 2 (7th January 2021) - French, William E
Abstract: Doña Carlota Yñiguez de Gil's death and her resurrection in textual form in the courtship diary of Luciano Gallardo and Carlota Gil, a twelve-volume tome written in and around Guadalajara, Jalisco, Mexico, between 1864 and 1869, offer a unique perspective on broad questions taken up in the literature on death and deathways in Mexico and elsewhere. Doña Yñiguez de Gil has much to say about ideologies of rule and understandings of piety at a point in time when, in Mexico, both death and marriage were shifting from ecclesiastical to civil control. Yet, her role as an active agent in history extends far beyond that of exemplary case in these paradigmatic shifts in politics and piety. A community of memory, one comprised of family, friends, neighbors, and others, grew up around her; through their ongoing relationship with her corpse, a social being, they found a powerful means to help them constitute identities of gender, family, class, community, and citizenship. Along with her grave and some of her possessions, she became a site of affect around whom a web of narratives, ideas, and values formed. Feelings accumulated around her as did a cluster of promises, including those of happiness, legitimacy, and acceptable family formation. The omnipresence of the deceased Doña Yñiguez de Gil in the diary, and her perceived role of intervening on the couple's behalf from on high, was also central to structuring remembrance, commemoration, a particular sense of time, and even the values and meanings of romantic love.